Study on the seismic performance of regional confined concrete columns. (December 2022) - Meng, Longfei; Zhu, Lihua; Zhu, Mingzeng
Abstract: This paper experimentally investigated the seismic performance of three regional confined concrete columns (RCCCs) and three normal confined concrete columns (NCCCs) subjected to low cyclic loading under a high axial compression ratio. The crack development and failure mode were studied. The effects of the axial compression ratio and stirrup form on the behavior (i.e., hysteretic behavior, stiffness, ductility and energy dissipation) of confined concrete columns were studied. The experimental results suggest that both NCCCs and RCCCs have good bearing capacity and ductility, and their failure modes are similar. At the same axial pressure ratio, the ductility and energy dissipation capacity of RCCCs are 5% and 10% higher than those of NCCCs respectively. The best load carrying capacity and energy consumption of the confined concrete columns are achieved when the axial compression ratio is 1.1. Furthermore, a finite element analysis was conducted to simulate the behavior of the RCCC. The results of the finite element analysis agree with the test results. The simulated results show that the peak load and cracking load of the RCCC decrease with increasing stirrup spacing.